Relationship between body positioning, muscle activity, and spinal kinematics in cyclists with and without low back pain. A systematic review - Streisfeld, G. M.; Bartoszek, C.; Creran, E.; Inge, B.; McShane, M. D.; Johnston, T. (Sports Health: A Multidisciplinary Approach, 2017)
Low back pain is reported by more than half of cyclists. The pathomechanics and association of risk factors of lumbar spine overuse injuries in cycling are not clearly understood. Objective: To determine whether relationships exist between body positioning, spinal kinematics, and muscle activity in active cyclists with nontraumatic low back pain. Data Sources: In August of 2015 and April of 2016, a comprehensive search of the PubMed, CINAHL, Ovid MEDLINE, and Scopus databases was performed independently by 5 reviewers. Study Selection: Included articles consisted of biomechanical studies examining factors relating to low back pain in cyclists as agreed upon by group consensus. Study Design: Systematic review. Level of Evidence: Level 4. Data Extraction: Five reviewers appraised by consensus each article using the Downs and Black checklist. Results: Eight studies met criteria for this review. There is evidence that cyclists with lower handlebar heights displayed increased lumbosacral flexion angles during cycling. Core muscle activation imbalances, back extensor endurance deficits, and increased lumbar flexion while cycling were found to be present in cyclists with low back pain. Conclusion: Spinal and core muscle activation imbalances in a prolonged flexed posture associated with cycling may lead to maladaptive spinal kinematics and increased spinal stresses contributing to overuse low back pain.